1982
DOI: 10.1002/ijc.2910290613
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tumor antigens by syngeneic antiserum on in vitro, transformed tracheal epithelial cell line 2‐10‐1

Abstract: Sera obtained from rats showing transplantation immunity to syngeneic, malignant epithelial cell line, 2-10-1, were used to identify antigens associated with transformation in vitro. The 2-10-1 cell line was derived from exposure of tracheal explants, in vitro, to the carcinogen MNNG. Tumorigenic passages of the cell line were shown to have common antigenic determinants, shared by independently transformed malignant tracheal epithelial cell lines, as well as antigenic determinants that appear to be limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
1984
1984

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Antibodies with sufficient specificity for identifying cell types that participate in the neoplastic process are potentially useful as markers to study the evolution of neoplastic disease. Previous studies demonstrated that carcinogen-induced respiratory tract carcinomas possess common tumor-rejection antigens and are capable of stimulating both cellular and humoral immune response in syngeneic animals (Jamasbi and Nettesheim, 1977;Jamasbi et al, 1978;Braslawsky et al, 1981Braslawsky et al, , 1982b. Using the polyclonal antibody response, we detected antigens on cell lines derived from DMBAand M"G-exposed F344 rat tracheal epithelial cells at both non-tumorigenic (early) and tumorigenic (late) passage levels (Braslawsky et al, 1982b).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Antibodies with sufficient specificity for identifying cell types that participate in the neoplastic process are potentially useful as markers to study the evolution of neoplastic disease. Previous studies demonstrated that carcinogen-induced respiratory tract carcinomas possess common tumor-rejection antigens and are capable of stimulating both cellular and humoral immune response in syngeneic animals (Jamasbi and Nettesheim, 1977;Jamasbi et al, 1978;Braslawsky et al, 1981Braslawsky et al, , 1982b. Using the polyclonal antibody response, we detected antigens on cell lines derived from DMBAand M"G-exposed F344 rat tracheal epithelial cells at both non-tumorigenic (early) and tumorigenic (late) passage levels (Braslawsky et al, 1982b).…”
mentioning
confidence: 89%
“…An indirect radioisotope assay using 1251-labelled rabbit anti-mouse IgG (for detection of mouse-derived MoAb) or 1251-labelled goat anti-rat IgG (for detection of rat-derived MoAb) was used to determine MoAb binding activity for various target cells (Braslawsky et al, 1982b).…”
Section: Antibody Binding Test (Abt)mentioning
confidence: 99%